Financial Distress: The Impact of the US-China Trade War on German Automotive Companies - Nina Titirai Tambung; Fitria Husnatarina; Muhammad Ichsan Diarsyad; Theresia Mentari (Manunggal Halim Jaya, 2026)
One indicator of financial distress is a decline in corporate financial performance, which can threaten the continuity of business operations. This issue is particularly critical for the German automotive industry, especially under external pressures such as the trade war between the US and China, which has caused reduced export demand, disruptions in the supply chain, and increased production costs. These challenges necessitate that companies strengthen corporate governance and utilize their resources efficiently to preserve financial stability. By incorporating firm size as a moderating variable, this study investigates the effect of corporate governance which encompasses the Board of Commissioners, Board of Directors, and Audit Committee on financial distress among German automakers listed on the DAX Automobile Index during 2018-2023. A total of 10 automotive companies were chosen as the research sample through purposive sampling and analyzed using EViews 12. The findings reveal that the Board of Directors has a significant negative effect on financial distress, while the Audit Committee and Board of Commissioners show no significant impact. Firm Size moderates the effect of the Board of Directors on financial distress, but it does not moderate the influence of the Board of Commissioners or the Audit Committee. Overall, the results highlight that the role of the Board of Directors is a key factor in preventing financial distress, particularly for automotive companies operating amid the US-China trade war. The results of this study can also be considered by management and regulators in strengthening corporate governance mechanisms to maintain financial stability.